(untitled) (Baghdad Science Journal, 2024)
The research was carried out at Al-Hanadi Research Station - Lattakia Agricultural Scientific Research Center, during spring season 2020 .To experience the effect of different potassium humate levels 500,1000,1500 ppm as a foliar spray on potato leaves variety Spunta , at 40 and 80% of field capacity humidity . The research involved four treatments with 3 replicates at each irrigation level. A Completely Randomized design was used. Plants were sprayed with potassium humate HA three times, with an interval of ten days after 35 days of planting. The results showed that water stress caused an increase in total soluble sugars, proline content and catalase activity in Spunta potato leaves, but total chlorophyll content was decreased. Potassium humate treatments improved biochemical parameters at 40% of field capacity. Potassium humate 1000 ppm treatment increased significantly total chlorophyll content 0.142 mmol/mg, and total soluble sugars 1.67mg/g in Spunta leaves ,while 1500 ppm treatment increased significantly proline content 45.65 ppm and catalase activity 0.04 mg/g at the same level 40% . Also, at 80% of field capacity, potassium humate 1000 ppm increased the total chlorophyll content 0.140 mmol/mg and proline content in potato leaves 11.63 ppm. Thus, potassium humate can be applied at a concentration 1000 and 1500 ppm to enhance the efficiency of potato plant Spunta tolerance under water shortage conditions.